Low Energy Modes of the Hydrogen-Bonded Dimer of Benzoic Acid. Issue 3 (1983) - Poeltl, David E.; McVey, Jeffrey K.
Abstract : Hydrogen bonding in isolated, cooled dimers of benzoic acid is explored following preparation in a free jet expansion. Analysis of the laser excitation spectrum in the low energy region allows for the identification of the modes involved in hydrogen bonding in the excited state of the dimer, and cluster formation is noted between the ground state dimers. Van der Waals complexes of the dimer with rare gas atoms are also identified. Assignments of the observed dimer modes have been made and the results are compared with previous studies in solution and matrices and with normal mode analyses.